‘Unsafe’ nutraceuticals products on the Internet: The need for stricter regulation in Malaysia - Daud, Mahyuddin; Abd. Jalil, Juriah; Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Safuan, Sahida (Institute of Electrical and Electronics Engineers Inc., 2017)
Nutraceutical products are functional foods consumed by many for its proclaimed benefits to health. Most nutraceutical products are not pharmaceutical drugs, hence has been treated as food. This made nutraceutical regulation more difficult since they do not fall under the jurisdiction of pharmaceutical regulatory authorities. Accordingly, Control of Drugs and Cosmetics Regulation 1984 and related legislations do not bind nutraceutical producers. This puts them away from direct monitoring and supervision from the Drug Control Authority (DCA). It is feared that lack of monitoring, unsupervised and unregulated production of nutraceutical products in a long run and for a long use could harm consumers. To add to the problem, nutraceutical products have been easily marketed through social media. Online sellers made ‘attractive’ claims that these products could cure even the most serious diseases. This paper examines the definitions of nutraceutical products and its regulatory frameworks in popular jurisdictions. It then proceeds to highlight the problem in lack of regulatory controls over nutraceutical products, which causes harms to consumers. This is worsened when social media has been effectively used to market these products – where some online sellers went up to the extent of making false claims to attract customers’ attention. The paper concludes with the finding that Food Act 1983 needs to address purchases of nutraceutical products through online channels. In particular, when a product was found to make false claims, the Food Act 1983 must also be empowered to have notice and takedown procedures – so that online customers will not be deceived by such claims.